Village level value chain upgrading for linking farmers to markets in Myanmar - CGIAR Research Program on Rice (2019)
Proof of concept in Bogale village in Myanmar with farmers participating in the activities adding US$140/ha profit by selling high quality milled rice to premium market in Yangon compared to selling paddy to local traders.